2013
DOI: 10.1111/agec.12003
|View full text |Cite
|
Sign up to set email alerts
|

Welfare implications of reduced government subsidies to farm families: accounting for fringe benefits

Abstract: In the past three decades, farm families have relied on government payments and off-farm income to reduce income risk and increase total household income. Studies have shown that, as the income effect dominates, government payments tend to reduce off-farm labor of farm operators and spouses. But that may not be true if one accounts for fringe benefits associated with off-farm employment. Additionally, with looming budget deficits and the possibility of a reduction in decoupled government payments, farm familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Jensen and Salant (1985) found that the fringe benefits offered by nonfarm-sector employment would increase the probability of farm exits in the US. This result is also supported by other studies on the impact of fringe benefi ts (such as employer-provided health insurance) on off-farm hours worked by US farm operators and their spouses (Ahearn et al, 2013;D'Antoni and Mishra, 2013;D'Antoni et al, 2014). Chang et al (2014) examined the impact of national health insurance reform in Chinese Taiwan and found that farmers increase the on-farm work days after they obtained the health insurance provided by the government.…”
Section: New Cooperative Medical Scheme In Chinasupporting
confidence: 66%
“…Jensen and Salant (1985) found that the fringe benefits offered by nonfarm-sector employment would increase the probability of farm exits in the US. This result is also supported by other studies on the impact of fringe benefi ts (such as employer-provided health insurance) on off-farm hours worked by US farm operators and their spouses (Ahearn et al, 2013;D'Antoni and Mishra, 2013;D'Antoni et al, 2014). Chang et al (2014) examined the impact of national health insurance reform in Chinese Taiwan and found that farmers increase the on-farm work days after they obtained the health insurance provided by the government.…”
Section: New Cooperative Medical Scheme In Chinasupporting
confidence: 66%
“…Namun, dari ketiga jenis kerja sama ini mereka memiliki konsep sipallambi melakukannya karena maksud membantu yang lainnya baik dari sisi tenaga maupun dari sisi materi (Vel & Bedner, 2015 Mentode adalah bentuk kerja sama antara pemilik dan petani penggarap dengan menghitung berapa luas lahan yang diselesaikan. Dalam hal ini mereka yang memiliki lahan saling bergantian membantu mengerjakan lahan pertanian dengan tujuan pengeloaan lahan pertanian lebih efisien (Alfian, 2013;D'Antoni & Mishra, 2013;Mulawarman & Kamayanti, 2018;Soonthornchai, 2017;Vel & Bedner, 2015;Suryanto, 2015;Yusof et al, 2015).…”
Section: Koleksi Data Seleksi Kodingunclassified
“…Another strand of literature focuses on the influence of decoupled payments on and offfarm labor supply decisions. Like fringe benefits, conservation payments receipts can be considered additional income providing incentives to decrease off-farm labor supply (Ahearn, El-Osta and Dewbre, 2006;D'Antoni and Mishra, 2013). For example, Ahearn et al (2006) used ARMS data for the years 1996 and 1999, reporting that production flexibility contract (PFC), loan deficiency payments (LDP), and market loan assistance (MLA) payments, individually and in aggregate, reduce the probability of the farmer to work off the farm.…”
Section: Introductionmentioning
confidence: 99%